PERANAN UNI EROPA MELALUI PROGRAM IPA (INSTRUMEN PRE-ACCESSION ASSISTANCE) DALAM MEMBANGUN PEREKONOMIAN KOSOVO - Miranti Purnamasari (Universitas Komputer Indonesia, 2018)
The problem of this research is how the European Union is a regional organization that is in the European region, has a policy of enlargement, which is a policy where the EU is trying to expand the area of cooperation to do so will be more extensive. Balkan region did not escape the attention of Europe. for this region, the European Union issued a Stabilisation and Association Process (SAP) which merupaka a policy that contains the promise of the EU to the Western Balkan countries for the opportunity to become a member. That's why Kosovo had finally become part of the SAP. After becoming a part of SAP, Kosovo received assistance from the EU as a potential candidate candidate. Program assistance provided by the EU is the IPA program which is a program set up to create a single framework to assist candidate countries and potential countries to join the EU premises. Through this IPA, the EU provides financial assistance to Kosovo to build its economy. This type of research is qualitative. The method used is descriptive analysis techniques. Most of the data collected through literature, as well as the search website. The results of this study indicate that the funds provided by the European Union through the IPA program provided through economy of Kosovo has been quite successful with demonstrated through improvements to the economy of Kosovo, the provision of this assistance has resulted in significant improvements in economic growth and development of Kosovo.